2017
DOI: 10.1177/0884533617692527
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk Screening 2002, Short Nutritional Assessment Questionnaire, Malnutrition Screening Tool, and Malnutrition Universal Screening Tool Are Good Predictors of Nutrition Risk in an Emergency Service

Abstract: The MUST, MST, and SNAQ share similar accuracy to the NRS-2002 in identifying risk of malnutrition, and all instruments were positively associated with very long hospital stay. In clinical practice, the 4 tools could be applied, and the choice for one of them should be made per the particularities of the service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 30 publications
3
55
0
7
Order By: Relevance
“…However, in studies carried out by Burgos et al 12 , Gobbardo and Boscaini 38 and Rabito et al 39 nutritional risk was observed in only, 28.9%, 14.8% and 29.3% of the patients, respectively.…”
Section: Weight Loss In the Last 3 Months Reduction Of Food Intake Inmentioning
confidence: 86%
“…However, in studies carried out by Burgos et al 12 , Gobbardo and Boscaini 38 and Rabito et al 39 nutritional risk was observed in only, 28.9%, 14.8% and 29.3% of the patients, respectively.…”
Section: Weight Loss In the Last 3 Months Reduction Of Food Intake Inmentioning
confidence: 86%
“…In a recent study evaluating the ability of tools to identify malnutrition based on the new ESPEN criteria, the MUST performed better than the NRS 2002, with higher sensitivity and specificity . In another study, Rabito et al compared the accuracy of 3 screening tools against NRS 2002 to identify patients at risk of malnutrition and the ability to predict morbidity and mortality. The authors found that the relative frequency of patients at nutrition risk differed between the screening tools, that MUST had the highest sensitivity and specificity, but that all tools showed moderate agreement and a satisfactory performance to identify patients at nutrition risk.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the relative frequency of patients at nutrition risk differed between the screening tools, that MUST had the highest sensitivity and specificity, but that all tools showed moderate agreement and a satisfactory performance to identify patients at nutrition risk. In their final adjusted univariate analysis, a significant association between nutrition risk and death was observed only with the MUST, which demonstrated a 2.34‐fold‐increased risk of mortality . Researchers have suggested that the MUST has performed better than NRS 2002 in trials because NRS 2002 relies on subjective evaluation of disease severity and may add a degree of bias, especially for conditions not specifically listed under the list of clinical states .…”
Section: Discussionmentioning
confidence: 99%
“…A lack of knowledge about nutrition and the nurses' high workload can lead to underdiagnosed and undertreated malnutrition [21][22][23]. The systematic use of assessment instruments, such as Nutritional Risk Screening (NRS 2002) [24]; the Short Nutritional Assessment Questionnaire (SNAQ) [25]; the Mini Nutritional Assessment (MNA) [26]; or the Malnutrition Universal Screening Tool (MUST) [27], can help to identify malnutrition in patients [28]. However, what if the situation is not recognized or is misinterpreted?…”
Section: Review Of the Literaturementioning
confidence: 99%